Peran Strategis Perempuan dalam Membangun Ketahanan Psikososial Anak Pascabencana melalui Pendidikan Dasar - Maisura; Juliana Putri; Maitanur; Abdul Ghani; Ja’far Nasution; Darmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasingly frequent hydrometeorological disasters in Indonesia, particularly in Aceh, have serious psychosocial impacts on elementary school-aged children, directly impacting the continuity of the learning process. This study aims to analyze the strategic role of women in building post-disaster psychosocial resilience in children through basic education by examining the underlying social, cultural, and religious dimensions. The study used a qualitative method with a field research approach, collecting data through in-depth interviews, participant observation, and documentation studies with female companions, elementary school-aged children, and community leaders in Alue Kuta Village, Bireuen Regency. The results indicate that post-disaster children experience anxiety, fear, impaired concentration in learning, and a decreased sense of security. Women emerge as the primary actors in psychosocial support through maternal relationships, emotional closeness, and informal educational practices based on Islamic values. The main findings reveal that women's mentoring, imbued with the values ​​of mercy, patience, and religious coping, effectively restores children's emotional stability, strengthens social adaptation, and encourages the sustainability of post-disaster basic education. This research highlights the importance of integrating women's roles and a religious-based psychosocial approach into basic education and disaster management policies to ensure holistic, sustainable, and aligns children's recovery with the Islamic culture and values ​​prevalent in the community. Keywords: Children, Disaster, Education, Women, Psychosocial.